2009
DOI: 10.1677/joe-09-0266
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal insulin receptor substrate 2 (IRS2) expression is regulated by ZBP89 and SP1 binding to the IRS2 promoter

Abstract: Since neuronal insulin receptor substrate 2 (IRS2)-mediated signals coordinate key processes in rodent physiology such as food intake, fertility, longevity, and aging-related behavior, we analyzed the mechanisms of neuronal IRS2 expression in neuroblastoma (SHSY5Y) and hypothalamic (GT1-7) cell lines. Using dual luciferase reporter assays and IRS2 promoter deletion constructs, we identified a regulatory cassette within the IRS2 promoter between K779 and K679 bp from the translational start which is responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…These findings suggest that the ZBP-89 gene functions as both an oncogene and anti-oncogene. Additionally, ZBP-89 binds to the neuronal IRS2 promoter and inhibits the activation of IRS2 (37). Our data showed that the introduction of siR-ZBP-89 into Mewo cells enhanced their IRS2 and phospho-Akt expression levels.…”
Section: Discussionmentioning
confidence: 58%
“…These findings suggest that the ZBP-89 gene functions as both an oncogene and anti-oncogene. Additionally, ZBP-89 binds to the neuronal IRS2 promoter and inhibits the activation of IRS2 (37). Our data showed that the introduction of siR-ZBP-89 into Mewo cells enhanced their IRS2 and phospho-Akt expression levels.…”
Section: Discussionmentioning
confidence: 58%
“…Jak2 tyrosine phosphorylation in the CNS also leads to phosphorylation of IRS2 protein which binds to the regulatory subunit (P85) of phosphatidylinositol 3-kinase (PI3K) and activates the catalytic domain of this intracellular enzyme, initiating a cascade of downstream kinases that regulate ion channel activity, gene transcription, and protein translation 7, 8 .…”
Section: Introductionmentioning
confidence: 99%
“…ZBP89 inhibits cell growth via the repression of gastrin and ornithine decarboxylase [25,26]. More recently, [28] revealed that neuronal insulin receptor substrate 2 (IRS2) expression is regulated by ZBP89 and Sp1 binding to the IRS2 promoter. A regulatory cassette composed of four ZBP89/SP1 binding sites controlled the IRS2 promoter activity in response to the PI3K pathway activation.…”
Section: Discussionmentioning
confidence: 99%